Predefined-time trajectory tracking control of free-flying space manipulator subject to uncertainties and disturbances - Yao, Qijia; Li, Qing; Huang, Mingji; Jahanshahi, Hadi (Robotics and autonomous systems, 2024)
This article addresses the predefined-time trajectory tracking control of free-flying space manipulator (FFSM) subject to uncertainties and disturbances. First, a predefined-time nonsingular terminal sliding mode (NTSM) controller is developed with the high insensitivity to uncertainties and strong robustness against disturbances. The generalized attitude and angular velocity tracking errors under the predefined-time NTSM controller can stabilize to zero in predefined time. Then, an adaptive version of the predefined-time NTSM controller is presented. The parametric adaptation mechanism is incorporated to identify the square of the upper bound of the lumped unknown item. Thus, the predefined-time adaptive NTSM (ANTSM) controller is smooth with no obvious chattering phenomenon and can maintain the high tracking accuracy simultaneously. The generalized attitude and angular velocity tracking errors under the predefined-time ANTSM controller can stabilize to the minor bounded regions around zero in predefined time. Simulations are provided to demonstrate the exploited controllers.